Talvisota - Parikka, Pekka (Finland : Finnish Film Foundation ; National-Filmi, 1989)
Based on a novel by Antii Tuuri, Talvisota is a dramatized commemoration the 1939 Russo-Finnish war. Threatened with total annexation, Finland courageously faced down the Soviet forces, despite being outnumbered 50 to 1. The tiny country loses the vital Karelian Isthmus, but Finland remains an independent nation, never falling into the Communist sphere as the Soviets had intended. This long (3 hours plus) but never draggy film personalizes the war by concentrating on the exploits of one beleaguered resistance fighter (Taneli Makela). This is the first film made about this epic struggle; recounting the war from the soldiers' point of view, letting us experience the brutality of daily life in the trenches.
Duration: 02:05:00
Keywords: Fiction films